Analysis and Simulation of the Creeping Phenomenon of Roller Conveyor Chain based on Recurdyn - Liu Yu; Zhao Juntian (Jixie chuandong)
The creeping phenomenon is a common instability phenomenon of chain transmission. Because of the roller conveyor chain often use to transfer power and convey material in the low speed,heavy duty and poor working environment,it more easily happen the creeping phenomenon to affect the normal operation of the conveyor chain. Through analyzing the dynamics characteristic and building the dynamics model of the conveyor chain,the main reasons of why the roller conveyor chain occur the creeping phenomenon are the different friction condition,the system stiffness and dynamic load. Finally,based on the Recurdyn,a simulation model of the roller conveyor chain transmission is built and the relative conclusion is verified.